Prognostic Implications of Intraoperative Radiography of Thyroidectomy Specimens. (2nd September 2014) - Frank, Robert; Fitzgerald, Ryan; Bodenner, Donald L.; Stack, Brendan C.
Abstract : Objectives: (1) Analyze radiographic findings of thyroidectomy specimens. (2) Correlate intraoperative radiography to preoperative ultrasound and its guided fine‐needle aspiration biopsy, intraoperative impression, and final pathology. (3) Describe a new intraoperative tool to help identify malignant characteristics of thyroid tissue. Methods: Prospective study comprised of consecutive patients undergoing hemi‐ or total thyroidectomy in a tertiary referral center. This is an ongoing study of patients treated from the months of November 2013 to June 2014. After obtaining ultrasound‐guided fine needle aspiration biopsies that were indeterminate or confirmed malignancy, all patients received either a hemi‐ or total thyroidectomy. Prior to pathologic processing, the specimens were passed off the field and underwent intraoperative specimen radiography (IOSR) by the Faxitron Biovision (Tucson, Arizona), generating a plain radiograph. Radiographic characteristics were analyzed by a surgeon and radiologist and correlated with final pathologic diagnosis. Sensitivity, specificity, positive and negative predictive value, and accuracy of IOSR with regard to final pathology will be reported. Results: Adequacy of resection of tumors and the presence of microcalcifications are features assessed by IOSR which, when compared with a pathology gold standard, may allow for a intraoperative decision regarding surgery. This technology may reliably detect multifocal microcarcinomas, another indication for total thyroidectomy. This approach may reduce the number of diagnostic hemi‐thyroidectomies that require a later completion thyroidectomy. Conclusions: Intraoperative plain film radiography may be an effective tool in the risk stratification of thyroid specimens and could be used as an adjunctive measure to reduce the need of delayed completion thyroidectomy, depending upon permanent pathology.